A New Multivariable Grey Convolution Model Based on Simpson's Rule and Its Applications. (27th February 2020) - Ding, Song; Li, Ruojin
Abstract : Accurate estimations can provide a solid basis for decision-making and policy-making that have experienced some kind of complication and uncertainty. Accordingly, a multivariable grey convolution model (GMC (1, n )) having correct solutions is put forward to deal with such complicated and uncertain issues, instead of the incorrect multivariable grey model (GM (1, n )). However, the conventional approach to computing background values of the GMC (1, n ) model is inaccurate, and this model's forecasting accuracy cannot be expected. Thereby, the drawback analysis of the GMC (1, n ) model is conducted with mathematical reasoning, which can explain why this model is inaccurate in some applications. In order to eliminate the drawbacks, a new optimized GMC (1, n ), shorted for OGMC (1, n ), is proposed, whose background values are calculated based on Simpson' rule that is able to efficiently approximate the integration of a function. Furthermore, its extended version that uses the Gaussian rule to discretize the convolution integral, abbreviated as OGMCG (1, n ), is proposed to further enhance the model's forecasting ability. In general, these two optimized models have such advantages as simplified structure, consistent forecasting performance, and satisfactory efficiency. Three empirical studies are carried out for verifying the above advantages of the optimized model, compared with the conventional GMC (1, n ), GMCG (1, n ), GM (1, n ), and DGM (1, n ) models. Results show that the new background values can effectively be calculated based on Simpson's rule, and the optimized models significantly outperform other competing models in most cases.